Nanorobots for in vivo monitoring: the future of nano-implantable devices - Gandhi, Mamta; Nigam, Preeti (Nanobiomaterial Engineering, 2020)
Innovation is important for the healthcare system advancement, in order to continue delivering the high-quality care at an affordable cost to the society. It can be achieved by nonconventional thinking, tapping into creative minds, and extensive collaborative work to make better use of existing facilities and designing new technologies. Nanorobotics is such an innovation that can revolutionize the current face of medicine and biomedical sciences with their state-of-the-art technology. Improved outcomes of nanorobots-based treatments for diabetes, drug delivery for pancreatic and ovarian cancer, and laparoscopic treatment of skin cancer have already been reported. This book chapter will cover the recent advancements of this emerging field with their biomedical applications.